Contribution to the knowledge of Tenuibaetis Kang & Yang 1994, Nigrobaetis Novikova & Kluge 1987 and Labiobaetis Novikova & Kluge 1987 (Ephemeroptera: Baetidae) from the Western Ghats (India) - Kubendran, T.; Balasubramanian, C.; Selvakumar, C.; Gattolliat, J. L.; Sivaramakrishnan, K. G. (Zootaxa, 2015)
As part of ongoing exploration of the mayflies of hill streams of southern Western Ghats, we describe two new species: Nigrobaetis paramakalyani Kubendran & Balasubramanian n. sp. and Labiobaetis jacobusi Kubendran & Balasubramanian n. sp. The genus Nigrobaetis is reported for the first time from India. Tenuibaetis frequentus (Müller-Liebenau & Hubbard 1985) n. comb. was also collected in this area and we provide the first description of this species at the imaginal stage. Brief ecological notes of the three species are added.